Electricity metering data exchange. The DLMS/COSEM suite. Mapping between the Common Information Model message profiles (IEC 61968-9) and DLMS/COSEM (IEC 62056) data models and protocols Part 6-9, (31st May 2016) - British Standards Institution,
No abstract available